Living in the New Creation: The Household Code in Ephesians as Theological Instruction - Andrew Montanaro (Religions)
The epistle to the Ephesians, like other Christian texts, teaches that life in the new creation, although not yet fully manifest, is already powerfully and sufficiently available to the church. However, this epistle uniquely has the predominant description of this new life in terms of entering into the household, or family, of God. Ephesians 1–5 makes this evident in the specific use of family language, the clustering of certain word groups (such as terms associated with wrath and peace), and the connection between promise and inheritance. This paper focuses on the instructions to children and fathers (Eph 6:1–4), showing that the teaching on the church in familial terms as the locus of the new creation is intended to be the basis for the way children and fathers are commanded to live their new life in their families. The description of the church contrasts with that of those outside the church, indicating that Christians are adopted children of God the Father, while those outside are “sons of disobedience” (2:2) and “children of wrath” (2:3). The instructions for children to be obedient and for fathers not to provoke their children to anger are best understood in this context.